Geochemical impacts of hydrothermal activity on surface deposits at the Southwest Indian Ridge. (September 2018) - Pan, Anyang; Yang, Qunhui; Zhou, Huaiyang; Ji, Fuwu; Wang, Hu; Pancost, Richard D.
Abstract: Submarine hydrothermal circulation has attracted much scientific interest since seafloor hydrothermal activity was first observed in the 1970s; an area of particular interest is the impact of exported inorganic and organic materials from hydrothermal vent systems into the open ocean. In 2007, the first active hydrothermal vent field, with vent fluid temperatures up to 379 °C, was discovered at the ultraslow spreading Southwest Indian Ridge (SWIR), where active vents are much less abundant than fast spreading ridges, and the effect of hydrothermal extrusion on surface sediments is not fully understood. To explore how geochemical proxy signatures respond to hydrothermal activity, we investigated the distributions of elements, minerals and lipids in surficial normal marine sediments, metalliferous sediments and low-temperature hydrothermal deposits collected from the SWIR. The results showed different effects of hydrothermal activity on the surface deposits. The normal marine sediments were predominantly calcium carbonate characterized by > 42% CaO and > 90% calcite, with a significant autochthonous marine contribution to organic matter (OM) and a predominance of lower molecular weight alkanols and fatty acids; they were uninfluenced by hydrothermal activity but received some terrigenous input represented by abundant high molecular weight n -alkanes with an odd-over-even predominance. The near-field metalliferous sediments and hydrothermal deposits were very different. Some near-field metalliferous sediments were influenced by low-temperature hydrothermal activity, and their distributions of elements and minerals were similar to those of hydrothermal deposits, which were characterized by abundant Fe/Si and opal/nontronite. Other near-field metalliferous sediments were evidently influenced by mixing of high-temperature hydrothermal sulfides typically containing abundant Cu/Zn. With respect to the organic matter assemblages, near-field deposits contained little evidence for thermal maturation of organic matter and all were characterized by a strong microbial signature, including hopanoids, isoprenoidal and non-isoprenoidal dialkyl glycerol ether lipids, and low molecular weight n -alkanes with an eve n carbon number predominance. The far-field metalliferous sediments, despite the influence of non-buoyant plumes and slightly higher concentrations of hydrothermal-derived metals (e.g., Fe, Cu and Zn), had the same distribution of organic lipids and major mineral composition (> 90% calcite) as did normal marine sediments. Thus, the influence of non-buoyant plume inputs appears to have been minimal possibly due to the dilution of in situ microorganisms by normal marine organisms in sediment and seawater. Furthermore, these characteristics indicate inorganic indices based on abundant metal elements derived from the hydrothermal systems (such as Fe/Cu/Zn content, ∑REE/Fe, the ternary diagram of Fe, Cu×100 and Ca) are more sensitive, serving as better proxies than organic matter assemblages to differentiate the effects of diverse hydrothermal activity on surface deposits. Highlights: Element, mineral and lipid distributions are distinct among diverse sediment types at SWIR. Metal element proxies can distinguish diverse types of hydrothermal impacts on sediments. Non-buoyant plumes have limited potential to influence the organic matter composition of far-field deposits. In situ microorganisms significantly contribute to the OM of near-field deposits.